Peran Kecerdasan Emosional Aparatur Sipil Negara dalam Meningkatkan Kualitas Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Buol: studi pada Aparatur Sipil Negara di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Buol - Serly Sihira; Sri Yanti UM. Armen; Sutra pattajani (Journal of Innovative and Creativity, 2025)
This study aims to analyze the role of emotional intelligence among civil servants (ASN) in improving the quality of public services at the Population and Civil Registration Office (Disdukcapil) of Buol Regency. The background of this research stems from the phenomenon of public service challenges, such as unresponsive attitudes of officials and suboptimal communication. This study employs a descriptive qualitative approach using in-depth interviews, observations, and documentation. The research informants consist of the head of the office, the head of the service division, ASN service staff, and members of the public using the services. The findings show that emotional intelligence plays an essential role in improving professionalism and the quality of interactions between officials and the community. Officials with strong self-awareness, empathy, and emotional regulation can deliver more effective, friendly, and satisfying services. Conversely, poor emotional control diminishes the public service image. This study emphasizes that developing emotional intelligence must be an integral part of human resource development to achieve quality, humanistic, and citizen-oriented public services. Keywords: Emotional Intelligence; Civil Servants; Public Service; Service Quality; Population and Civil Registration Office.